2018
DOI: 10.1186/s12961-018-0340-y
|View full text |Cite
|
Sign up to set email alerts
|

Are our ‘UHC systems’ learning systems? Piloting an assessment tool and process in six African countries

Abstract: BackgroundIf there is one universal recommendation to countries wanting to make progress towards Universal Health Coverage (UHC), it is to develop the learning capacities that will enable them to ‘find their own way’ – this is especially true for countries struggling with fragmented health financing systems. This paper explores results from a multi-country study whose main aim was to assess the extent to which UHC systems and processes at country level operate as ‘learning systems’.MethodThis study is part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…From the start, we aimed to make these CoPs much more than just online communities. We organised face-to-face meetings and workshops,8 conducted multi-country research,9–11 developed frameworks and training modules,12 broadcast webinars, organised a cartoon contest and carried out a range of other collaborative activities.…”
Section: Our Practice In Collective Learningmentioning
confidence: 99%
See 4 more Smart Citations
“…From the start, we aimed to make these CoPs much more than just online communities. We organised face-to-face meetings and workshops,8 conducted multi-country research,9–11 developed frameworks and training modules,12 broadcast webinars, organised a cartoon contest and carried out a range of other collaborative activities.…”
Section: Our Practice In Collective Learningmentioning
confidence: 99%
“…Such an information deficit is problematic, especially since UHC financing tends to be built out from existing schemes, not from scratch. So finding this deficit led CoP experts to yet another participatory study, focused on systemic learning capacities for UHC in six countries 11. It demonstrated that in these countries, ‘UHC systems’ were not yet full learning systems.…”
Section: Our Practice In Collective Learningmentioning
confidence: 99%
See 3 more Smart Citations